2022
DOI: 10.3389/fendo.2022.844707
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic IGF2/H19 Epigenetic Alteration Induced Glucose Intolerance in Gestational Diabetes Mellitus Offspring via FoxO1 Mediation

Abstract: ObjectiveThe offspring of women with gestational diabetes mellitus (GDM) have a high predisposition to developing type 2 diabetes during childhood and adulthood. The aim of the study was to evaluate how GDM exposure in the second half of pregnancy contributes to hepatic glucose intolerance through a mouse model.MethodsBy creating a GDM mouse model, we tested glucose and insulin tolerance of offspring by intraperitoneal glucose tolerance test (IPGTT), insulin tolerance test (ITT), and pyruvate tolerance test (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…As this region controls the H19 and IFG2 imprinting cluster, LOI is related to altered glucose metabolism and diabetes [ 50 ]. Intrauterine hyperinsulinemia changes H19DMR methylation in the foetuses which exhibited impaired glucose tolerance and insulin resistance [ 51 ]. Obesity is a risk factor for cancer in general and is associated with an increased risk of invasive penile cancer, inducing chronic inflammation and insulin resistance [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…As this region controls the H19 and IFG2 imprinting cluster, LOI is related to altered glucose metabolism and diabetes [ 50 ]. Intrauterine hyperinsulinemia changes H19DMR methylation in the foetuses which exhibited impaired glucose tolerance and insulin resistance [ 51 ]. Obesity is a risk factor for cancer in general and is associated with an increased risk of invasive penile cancer, inducing chronic inflammation and insulin resistance [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the upregulation of IGF2 in response to high-glucose conditions may be a feedback loop to increase the utilization of glucose and reduce the blood glucose level, which probably contributes to weight gain. A previous paper ( 26 ) indicated that male offspring of GDM mice have lower expression of IGF2 in the liver, and they show more severe glucose intolerance and insulin resistance than female offspring. Elevated IGF2 levels may be beneficial in stabilizing blood glucose concentrations, such as in the intrauterine hyperglycemic environment in women with GDM, but the consequence of this process affecting weight gain probably leads to macrosomia, which is an adverse pregnancy outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Other mouse models of GDM have sought to confirm this finding, and also noted offspring sex-specific differences in response to maternal hyperglycaemia. While IGT was reported in both male and female offspring, only male offspring demonstrated increased birth weight, increased gluconeogenesis, increased fasting insulin and decreased insulin sensitivity ( 132 ). In contrast to findings in the pancreas, hepatic expression of IGF2 and H19 was significantly higher in male offspring, with hypermethylation reported at IGF2 -DMR0 and IGF2 -DMR1.…”
Section: Subsectionsmentioning
confidence: 99%